2022
DOI: 10.1039/d2cp00993e
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark relativistic delta-coupled-cluster calculations of K-edge core-ionization energies of third-row elements

Abstract: A benchmark computational study of K-edge core-ionization energies for third-row elements using relativistic delta-coupled-cluster (ΔCC) methods and a revised core-valence separation (CVS) scheme is reported. High-level relativistic (HLR) corrections beyond...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…In a subsequent study, the same team found the relevance of going beyond S1 (CVS0 in their work) and using an equivalent to our S2 (CVS-ΔCCSD(T) in their work), they found excellent agreement with experiment as well. 107 The numbers they report on the third column of their Table 1, corresponding to their CVS-ΔCCSD(T) model with a TQ5-extrapolated cc-pCVXZ BSL, yield an MSE, MAE, and RMSE of 0.11, 0.13, and 0.17 eV for the subset of molecules common in both our data-sets (all of the ones presented here except Be and Ne,) using the experimental values we collected. Furthermore, they show that high-order relativistic effects ( i.e ., going beyond the exact two-component theory in its one-electron variant, or X2C-1e) are not relevant for second-row K-edge ionizations but they amount to −0.80 eV for Si, quickly increasing with the atomic number of the probed atom.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a subsequent study, the same team found the relevance of going beyond S1 (CVS0 in their work) and using an equivalent to our S2 (CVS-ΔCCSD(T) in their work), they found excellent agreement with experiment as well. 107 The numbers they report on the third column of their Table 1, corresponding to their CVS-ΔCCSD(T) model with a TQ5-extrapolated cc-pCVXZ BSL, yield an MSE, MAE, and RMSE of 0.11, 0.13, and 0.17 eV for the subset of molecules common in both our data-sets (all of the ones presented here except Be and Ne,) using the experimental values we collected. Furthermore, they show that high-order relativistic effects ( i.e ., going beyond the exact two-component theory in its one-electron variant, or X2C-1e) are not relevant for second-row K-edge ionizations but they amount to −0.80 eV for Si, quickly increasing with the atomic number of the probed atom.…”
Section: Resultsmentioning
confidence: 99%
“…This treatment of the correlation involving the virtual core orbital is closely related to that 55 employed by Matthews in their study of core excitations 67 via the state-specific two-determinant Hilbert-space MR-CC, 82,83 and by Zhang et al for DCCSD(T) core ionizations. 107 S2 is pleasing in that, even though core substitutions are involved, they are all associated with configurations that retain a core occupancy of 1.…”
Section: Approaches To Inclusion Of Corevalence Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis reveals that the spin-free X2C oneelectron Hamiltonian overbinds by 10.3 eV for Cu 2+ , which is comparable to the errors seen in Table 5. However, these contributions amount to 3.9 eV for Ti 4+ , indicating that they are very much relevant even for lighter elements (including the third period elements Si−Cl 122 ). It therefore appears that the good performance of OO-DFT/X2C in this regime is partly due to cancellation of errors between the missing relativistic contributions and the functional error from SCAN.…”
mentioning
confidence: 99%
“…To calculate the Br 1s and I 1s ionization energies of IBr, we began with the deltacoupled-cluster singles and doubles method augmented with a noniterative inclusion of triple excitations [∆ CCSD(T)] [21,22]. Scalar-relativistic effects were treated using the spin-free exact two-component theory in its one-electron variant (SFX2C-1e) [23,24].…”
Section: A Calculated Ionization Energiesmentioning
confidence: 99%